On the Lagrangian and Hamiltonian aspects of infinite-dimensional dynamical systems and their finite-dimensional reductions - Prykarpatsky, Y.A.; Samoilenko, A.M. (Нелінійні коливання, 2005)
Some aspects of the description of Lagrangian and Hamiltonian formalisms naturally arising from the
invariance structure of given nonlinear dynamical systems on the infinite-dimensional functional manifold is presented. The basic ideas used to formulate the canonical symplectic structure are borrowed
from the Cartan’s theory of differential systems on the associated jet-manifolds. The symmetry structure
reduced on the invariant submanifolds of critical points of some nonlocal Euler – Lagrange functional
is described thoroughly for both differential and differential discrete dynamical systems. The Hamiltonian representation for a hierarchy of Lax-type equations on a dual space to the Lie algebra of integraldifferential operators with matrix coefficients, extended by evolutions for eigenfunctions and adjoint eigenfunctions of the corresponding spectral problems, is obtained via some special Backlund transformation. The connection of this hierarchy with integrable by Lax spatially two-dimensional systems is studied. Наведено деякi аспекти опису лагранжевого та гамiльтонового формалiзму, який природно виникає iз структури iнварiантностi заданих нелiнiйних динамiчних систем на нескiнченновимiрному функцiональному многовидi. Основнi iдеї, якi використовуються для формування канонiчної симплектичної структури, взято з теорiї Картана диференцiальних систем на вiдповiдних многовидах струмiв. Для диференцiальних та диференцiальних дискретних динамiчних
систем наведено детальний опис структури симетрiй, якi редукованi на iнварiантнi пiдмноговиди критичних точок деяких нелокальних ейлерово-лагранжевих функцiоналiв. За допомогою
деякого перетворення Беклунда отримано гамiльтонове зображення для iєрархiї рiвнянь лаксового типу на двоїстому до алгебри Лi просторi iнтегрально-диференцiальних операторiв з
матричними коефiцiєнтами, яке продовжено еволюцiями власних функцiй та спряжених власних функцiй вiдповiдних спектральних задач. Вивчено зв’язок мiж цiєю iєрархiєю та iнтегровними за Лаксом просторово-двовимiрними системами.